Induced genetic variability for quantitative traits in M2 generation in soybean by mutagens - Wakode2, Geeta P. Patil1 and Manish M. (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The various genetic variability parameters were estimated using physical (gamma rays) and chemical (EMS) mutagens using two cultivars i.e. PKV-1 and JS-335. Results indicated that genotypic coefficient of variation and phenotypic coefficient of variation, heritability were significantly high for different characters studied i.e. Plant height, number of branches per plant, number of clusters per plant, number of pods per plant, yield per plant, 100 grain weight. All the mutagenic treatments were effective in inducing genetic variability in both the varieties.